A Reading Prerequisite Program to Improve Beginning Reading Ability of Dyslexia Students - Misdayani, Misdayani; Aprilia, Imas Diana; Hernawati, Tati (Department of Special Education, 2024)
Learning difficulties in the aspects of reading, writing or spelling (dyslexia) are cases that are often encountered and require special programmed treatment to optimize children's abilities in accordance with their age development. The purpose of this study is to describe the program aimed at one of the second grade students at SDN 195 Isola who has dyslexia and his reading ability is at the pre-requisite stage so that the researcher formulates a program that focuses on the reading aspect. The research method used is descriptive qualitative through in-depth observation, interviews, assessment and documentation studies to explore what students need. The research results obtained are a hypothetical program formulation consisting of rationale, objectives, materials, strategies, and evaluations that have been validated so that it is feasible to be a guide in implementing learning to improve students' pre-requisite reading skills.